Determining boride layer thicknesses formed on XC38 steel with artificial neural network - Yassine El Guerri; Bendaoud Mebarek (Zaštita Materijala)
Boride layers result from surface treatments of materials, offering valuable mechanical and tribological aspects that extend the material's life expectancy and potential. They are achieved by a process known as boriding in which boron atoms are diffused into the material until saturation, where a layer that may be mono or dual-phased begins to thicken over time depending on the period of treatment, the temperature held, the media applied, the composition of the material with its impurities, and more. Due to the difficulty of encompassing all those different parameters that influence the kinetic evolution of that boride layer, the idea was to start by training an artificial neural network to estimate its thickness with only two variables and inspect the results. Three experimental observations out of nine were used as validating data, while the rest were training data, along with others added. Depending on the reliability of the predictions given by the artificial neural network, further research can explore the possibilities of training it on different samples and environments through data mining.